2019
DOI: 10.47070/ijapr.v7i6.1211
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Enlisted Ayurvedic Lipid Lowering Herbs According to Principle of Ayurveda

Abstract: INTRODUCTION: Dyslipidemia is a condition marked by unhealthy abnormal concentrations of lipids in blood. There is no direct description of dyslipidemia in Ayurvedic texts. However Medo Rogas (Fat disorders) are described in Ayurvedic texts since ancient times. Dyslipidemia (Medo roga) is a disease of diminished Jatharagni, Bhutagni and Dhatwagni induced apachita or saam asthayi meda dhatu vriddhi. So for the management of Dyslipidemia (Medo roga) such drugs are needed which having Deepan, Pachan, Kaphaghna an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…Human examinations have uncovered that expanded fat admission is related with body weight acquire, which can prompt corpulence and other related metabolic illnesses. This examination hence demonstrated that rodents presented to highfat diet for about fourteen days cause a critical increment of creatures' body weight, along these lines confirming the stout status [15]. Despite the fact that there was asignificant difference in the body weights between the high-fat and normal diet groups, nosignificant difference was seen in the everyday food admission of creatures.…”
Section: Treated Ratsupporting
confidence: 54%
“…Human examinations have uncovered that expanded fat admission is related with body weight acquire, which can prompt corpulence and other related metabolic illnesses. This examination hence demonstrated that rodents presented to highfat diet for about fourteen days cause a critical increment of creatures' body weight, along these lines confirming the stout status [15]. Despite the fact that there was asignificant difference in the body weights between the high-fat and normal diet groups, nosignificant difference was seen in the everyday food admission of creatures.…”
Section: Treated Ratsupporting
confidence: 54%